PENGARUH INTELLECTUAL CAPITAL DAN KEBIJAKAN DIVIDEN TERHADAP KUALITAS LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dimita H. P. Purba; Putri J. Sitorus; Ivalda Equila Purba (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2022)
This study aims to determine and analyze the effect of intellectual capital and dividend policy on the earnings quality on pharmaceutical companies listed on Indonesia stock exchange. Determination of the sample used in this study is a purposive sampling technique totaling 5 (five) companies with seven years observation period and the data used is sourced from the annual report of pharmaceutical companies through the website www.idx.co.id. The data analysis method used in this research is multiple linear regression analysis. The result of research that partially intellectual capital with the indicator Value Added Capital Employed (VACA) has negative and insignificant effect on earnings quality, intellectual capital with the indicator Structural Capital Value Added (STVA) has negative effect and significant effect on earnings quality, dividend policy as measured by Dividend Payout Ratio (DPR) has positive and significant effect on earnings quality. The results of subsequent tests showed that VACA, STVA and DPR simultaneously had significant effect on the earnings quality on pharmaceutical companies listed on Indonesia stock exchange for the period 2014-2020.